Fertility, full-time and part-time female employment in Europe - Gomes, Cristina Sousa (2012)
This paper aims to analyse the relation between women’s employment patterns, more specifically part-time employment, and fertility trends in European countries, using Eurostat data. It is argued that this approach sheds an innovative light on the debate. The issue of part-time employment is put into perspective in the context of family policies and gender relations. The fertility/employment relationship shows that the overall positive association between fertility and female employment is a consequence of the importance of part-time employment and is not related with full-time employment. Therefore, the change in sign of the fertility employment association after the 1980s could result from the increasing diversification of the labour market.